2013
DOI: 10.3892/ijo.2013.2225
|View full text |Cite
|
Sign up to set email alerts
|

Snail-induced epithelial-mesenchymal transition promotes cancer stem cell-like phenotype in head and neck cancer cells

Abstract: Abstract. Head and neck squamous cell carcinoma (HNSCC) is known to have a poor prognosis. The resistance to treatment and distant metastasis are important clinical problems in HNSCC. The epithelial-mesenchymal transition (EMT) is a key process in successful execution of many steps such as the invasion and metastasis for cancer cells. Snail is one of the master regulators that promote EMT in many types of malignancies including HNSCC. Recently, it has been shown that Snail-induced EMT could induce a cancer ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 48 publications
(42 reference statements)
4
43
0
1
Order By: Relevance
“…10,11 EMT plays an important role in the metastasis of HNSCC by facilitating primary tumor invasion through the basement membrane and migration through the tumor-associated stroma or extracellular matrix (ECM). [12][13][14] It has been reported that DDR2 is a critical regulator of EMT. 15 Though previous studies have investigated the function of DDR2 in some common tumors, there has not been functional characterization of the potential role of DDR2 in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 EMT plays an important role in the metastasis of HNSCC by facilitating primary tumor invasion through the basement membrane and migration through the tumor-associated stroma or extracellular matrix (ECM). [12][13][14] It has been reported that DDR2 is a critical regulator of EMT. 15 Though previous studies have investigated the function of DDR2 in some common tumors, there has not been functional characterization of the potential role of DDR2 in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed that the low-score subtype was significantly enriched by a hypoxia-induced gene set in HNSCC (21). The cancer stem cell-like phenotype was associated with chemo-resistance in head and neck cancer cells (22)(23)(24). We found that two stemness expression signatures were enriched in the low-score phenotype.…”
Section: Main Effect Of Variablesmentioning
confidence: 62%
“…The changes in gene expression that contributed to the repression of the epithelial phenotype and activation of the mesenchymal phenotype involves the regulators Snail and Twist (33). Induction of Snail expression has been noted in all EMT processes that have been previously studied, and increased Snail levels have been correlated with more invasive tumor types (34)(35)(36). Snail regulated the expression level of epithelial or mesenchymal genes and it regulated the expression level of E-cadherin, which is downregulated during EMT (37).…”
Section: Discussionmentioning
confidence: 99%